Pharmacokinetics, mass balance, tissue distribution, metabolism, and excretion of praliciguat, a clinical‐stage soluble guanylate cyclase stimulator in rats. Issue 2 (20th April 2020) - Banijamali, Ali R.; Carvalho, Andrew E.; Wakefield, James D.; Germano, Peter; Barden, Timothy C.; Tobin, Jenny V.; Zimmer, Daniel P.; Masferrer, Jaime L.; Profy, Albert T.; Currie, Mark G.; Todd Milne, G.
Abstract: The pharmacokinetics (PK), metabolism, excretion, mass balance, and tissue distribution of [ 14 C]praliciguat were evaluated following oral administration of a 3‐mg/kg dose in Sprague‐Dawley rats and in a quantitative whole‐body autoradiography (QWBA) study conducted in male Long‐Evans rats. Plasma T max was 1 hour and the t 1/2 of total plasma radioactivity was 23.7 hours. Unchanged praliciguat accounted for 87.4%, and a minor metabolite ( N ‐dealkylated‐praliciguat) accounted for 7.6% of the total radioactivity in plasma through 48 hours (AUC0‐48 ). Tissues with the highest exposure ratios relative to plasma were liver, intestines, adrenal gland, and adipose, and those with the lowest values were seminal vesicle, blood, CNS tissues, lens of the eye, and bone. Most of the [ 14 C]praliciguat‐derived radioactivity was excreted within 48 hours after oral administration. Mean cumulative recovery of the administered radioactivity in urine and feces over 168 hours was 3.7% and 95.7%, respectively. Unchanged praliciguat was not quantifiable in urine or bile of cannulated rats; however, based on the total radioactivity in these fluids, a minimum of approximately 82% of the orally administered dose was absorbed. [ 14 C]Praliciguat was metabolized via oxidative and glucuronidation pathways and the most abundant metabolites recovered in bile were praliciguat‐glucuronide and hydroxy‐praliciguat‐glucuronide. These results indicate that praliciguat had rapid absorption, high bioavailability, extensive tissue distribution, and elimination primarily via hepatic metabolism.